2018
DOI: 10.1002/cctc.201702015
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Carbocatalysts for Thermoset Polymers and for Diastereoselective and Enantioselective Organic Synthesis

Abstract: This review reports on the catalytic activity of graphene oxide (GO) and high‐surface‐area graphite (HSAG) for some relevant organic reactions. It is shown that the main drawbacks of graphite‐based catalysts, that is, high catalyst loading and generally poor selectivity, can often be removed by operating under solvent‐free conditions. Moreover, some reactions that are catalyzed by GO as well as HSAG are presented. For these reactions, π stacking of the aromatic substrates with the graphitic planes plays a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Carbonaceous materials have emerged as promising green carbocatalysts in various organic reactions 18 . Graphene oxide (GO), a 2D, carbonaceous material bearing different oxygen functional groups such as alcohol, epoxide, ketones, and carboxylic acid 912 , is emerging as a green alternative for organic transformations and particularly superb in acidic carbocatalysis 5,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbonaceous materials have emerged as promising green carbocatalysts in various organic reactions 18 . Graphene oxide (GO), a 2D, carbonaceous material bearing different oxygen functional groups such as alcohol, epoxide, ketones, and carboxylic acid 912 , is emerging as a green alternative for organic transformations and particularly superb in acidic carbocatalysis 5,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Graphite-based materials are widely used for many applications, mainly as fillers in polymer matrices, because of their ability to improve the mechanical and physical properties. In the past decades, they attracted considerable attention for their possible application in many fields such as catalysis, energy storage and conversion, , water remediation, , and supercapacitors …”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have shown a catalytic activity of graphene oxide and of oxidized carbon black on the reaction between the epoxy and amine groups of the resin, leading to higher crosslinking density in milder conditions [12,13,14,15,16,17,18,19,20]. This catalytic activity, suggested by the well-established catalytic behavior of graphene oxide for many organic reactions [21,22,23,24,25,26,27,28,29,30,31,32], has been proved by experiments on the epoxide ring opening reaction, for monofunctional epoxide and amine reactants, which lead to an uncrosslinked product being suitable for full chemical characterization [17,19].…”
Section: Introductionmentioning
confidence: 99%